(untitled) (Ágora Journal, 2022)
The captaincy-generals and governors’ way to act and their trajectories are an important tool to discuss local power and their arrangements. Considering that the Portuguese empire was established as a complex governance network, we propose in this article analyze some manifestations of the administered from the time when the captaincy-generals and governors’ administration in the Captaincy of Paraíba in the first half of the seventeen hundred. To do so, we revised handwritten sources contained in the Arquivo Histórico Ultramarino and documents held by the Sesmarias do Império Luso-Brasileiro Platform, to examine the compliments and complaints against the regal administrators. Finally, it was verified that these documents, besides informing the crown on the performance of the governors’ conduct, also hid defense strategies of personal interests and privilege preservation.